2017 GPOH Guidelines for Diagnosis and Treatment of Patients with Neuroblastic Tumors - Simon, Thorsten; Hero, Barbara; Schulte, Johannes H.; Deubzer, Hedwig; Hundsdoerfer, Patrick; von Schweinitz, Dietrich; Fuchs, Jörg; Schmidt, Matthias; Prasad, Vikas; Krug, Barbara; Timmermann, Beate; Leuschner, Ivo; Fischer, Matthias; Langer, Thorsten; Astrahantseff, Kathy; Berthold, Frank; Lode, Holger; Eggert, Angelika (Klinische Pädiatrie, 2017)
The clinical course of neuroblastoma is more heterogeneous than any other malignant disease. Most low-risk patients experience regression after limited or even no chemotherapy. However, more than half of high-risk patients die from disease despite intensive multimodal treatment. Precise patient characterization at diagnosis is key for risk-adapted treatment. The guidelines presented here incorporate results from national and international clinical trials to produce recommendations for diagnosing and treating neuroblastoma patients in German hospitals outside of clinical trials.
Keywords: neuroblastoma; ganglioneuroma; childhood cancer; treatment recommendations